2001
DOI: 10.4049/jimmunol.167.4.2234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-4 in Heligmosomoides polygyrus-Induced Alterations in Murine Intestinal Epithelial Cell Function

Abstract: IL-4 and IL-13 promote gastrointestinal worm expulsion, at least in part, through effects on nonlymphoid cells, such as intestinal epithelial cells. The role of IL-4/IL-13 in the regulation of intestinal epithelial function during Heligmosomoides polygyrus (Hp) infection was investigated in BALB/c mice infected with Hp or treated with a long-lasting formulation of recombinant mouse IL-4/αIL-4 complexes (IL-4C) for 7 days. Separate groups of BALB/c mice were drug-cured of initial infection and later reinfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
140
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 23 publications
(18 reference statements)
10
140
0
1
Order By: Relevance
“…These findings expand those of our previous report (11) in two significant ways. First, our observation that IL-4 and IL-13 affect the intestinal epithelial secretory response to 5-HT is novel, in that it was not investigated in mice treated with anti-IL-4R␣ mAb.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings expand those of our previous report (11) in two significant ways. First, our observation that IL-4 and IL-13 affect the intestinal epithelial secretory response to 5-HT is novel, in that it was not investigated in mice treated with anti-IL-4R␣ mAb.…”
Section: Discussionsupporting
confidence: 91%
“…We showed previously that IL-4 mediates a decrease in glucose absorption and an increase in fluid secretion in mice infected with the gastrointestinal nematode parasite H. polygyrus, suggesting that this effect of IL-4 may contribute to IL-4-dependent worm expulsion (11). In this study, we compare the effects of in vivo administration of a long-acting formulation of IL-4 with the effects of in vivo administration of the related cytokine, IL-13, on intestinal epithelial cell function, and determine the contribution of STAT6 signaling to these cytokineinduced alterations in intestinal physiology.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, unlike T. spiralis, expulsion of N. brasiliensis does not depend on mast cells (32), and the cell type or factors that increase enteric leakiness during this infection remained undefined. Shea-Donohue et al (33) stimulated tissue from Heligmosomoides polygyrus-challenged mice with prostaglandin E2 and observed a rise in chloride ion secretion. This response was blocked when mice were treated with anti-IL-4 receptor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory cell infiltrate develops around the invading parasitic larvae, resulting in a border of cells that delineate a loosely defined, cyst-like structure (5,6). Although the mechanism of worm expulsion remains uncertain, direct effects of IL-4 and IL-13 on gut tissue are probably important (7)(8)(9), and some studies have suggested that an effective memory response is also associated with delayed larval development before emergence into the lumen (5,10). The CD4 T cell response has not been examined at peripheral sites of infection, but pronounced increases in CD4 T cell IL-4 and IL-13, but not IFN-␥, are detected in the mesenteric lymph node (MLN) as early as day 8 after primary inoculation and secondary challenge (11,12).…”
mentioning
confidence: 99%